Investigating fuel for firing pottery at the end of the 3rd mill. BCE: the case of Logardan, northern Iraq - Douche, C; Charles, M (Elsevier, 2023)
Fieldwork carried out by the French Qara Dagh Archaeological Mission at the tell site of Logardan in northern Iraq, has revealed an extensive pottery workshop (levels 3a-b), characterised by hundreds of pottery kilns dated to the end of the 3rd millennium BCE. This paper presents the archaeobotanical results related to these firing structures and associated contexts. Despite the location of the site on the foothills of the Qara Dagh mountains where wood fuel is expected to be available, wood charcoal is present in small quantities and is poorly preserved making it difficult to assess its role. Instead, the charred plant remains recovered are dominated by numerous tiny grass seeds (<1mm) or seeds possessing a thick (hard) seed coat that characterise livestock dung. Multi-variate comparison of the kiln deposits with the other contexts leads us to conclude that dung was used as the primary fuel for firing pottery. Reasons for this selection are considered based on ethnographic accounts of traditional pottery manufacture.